Vaginal trichomoniasis: what is up? - Bravo, Renato S.; Giraldo, Paulo C.; Carvalho, Newton S.; Gabiatti, José Roberto E.; Val, Isabel C.C.; Giraldo, Helena Patrícia D.; Passos, Mariana D.L. (Brazilian Journal of Sexually Transmitted Diseases, 2010)
This study is an updated review of Trichomonas vaginalis prevalence in the general population as well as its complex interaction with the host and the consequences of undiagnosed infection. The Trichomonas vaginalis is an extracellular parasite of the mucous membranes, especially the vagina, causing vaginal discharge, irritation and inflammation and may be asymptomatic in nearly one third of cases. Currently, little has been found in some centers, but remains a important cause of vulvovaginitis in the world keeping up with rates of 10% of vaginal discharge in several epidemiological studies. This involves complex host parasite relationship where the immune response predisposes to bacterial vaginosis and HIV infection by mobilizing defense cells (leukocytes, CD4 T lymphocytes and macrophages). The forms of diagnosis are pointed to facilitate understanding of the diagnosis. We also pointed the way to treatment and in particular the difficulties with cases of drug resistance.